Combined effect of anti-parasitic drugs to control argulosis in fish farms of Ganjam district, Odisha: Combined drugs against Argulus - Bera, Pujadebi; Udgata, Santosh Kumar; Nanda, Saumyendra; Sahu, Brundaban; Tripathy, Manoj Kumar; Patra, Sushanta Kumar (Journal of the Inland Fisheries Society of India, 2023)
The crustacean parasites play a major role in infection in fishes leading to mortality and economic loss in Aquaculture. Argulus spp. possesses a great threat among other ecto-parasites in fish. Fish farms of Ganjam district in Odisha were kept under surveillance for studying occurrence and recurrence of argulosis. All six fish farms were reported to have two species of Argulus. They were identified as A. siamensis and A. bengalensis based on the results of phenotypic characteristics under microscopy. Prevalence, abundance, and intensity of infection were found higher for A. siamensis than A. bengalensis. There were minimum two cases of Argulus infestation in each farm every year showing the recurrence of argulosis in Ganjam district. Two anti-parasitic drugs viz., cypermethrin (through immersion) and emamectin benzoate (through feed) were selected for individual and combined use. For individual use, doses were selected as 0.94 /L, 2.84 /L for cypermethrin and 161.41 /kg feed, 484.23 /kg feed for emamectin benzoate. Alternative doses of two drugs were used in single treatment for combined use and vice-versa in other treatment. In experimentally infected fishes, the parasites causing argulosis was identified to be A. siamensis. Parasite mortality rate varied between 74% and 87.2% against doses of cypermethrin of 0.94 /L and 2.84 /L respectively after 48h of treatment. While it varied between 81 and 88% for emamectin benzoate of 161.41 /kg and 484.23 /kg feed. Better efficacy was found in combined treatment. Combined treatment with dose of 2.84 /L cypermethrin and 161.41 /kg feed of emamectin benzoate showed better result with 100% parasite mortality after 48h post treatment. This dose was used in farm trial in Humari Fish Farm, Chhatrapur, Ganjam with 100% reduction in argulosis infestation within 7 days of treatment. Considering the effects, these two drugs may be recommended to use together for better management of argulosis in aquaculture ponds.